2018
DOI: 10.1001/jamaoncol.2018.2446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Lay Health Worker Intervention on Goals-of-Care Documentation and on Health Care Use, Costs, and Satisfaction Among Patients With Cancer

Abstract: ClinicalTrials.gov Identifier: NCT02966509.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 41 publications
(67 reference statements)
4
140
1
Order By: Relevance
“…A recent intervention using a lay facilitator demonstrated statistically significant differences in goals of care documentation, overall rating of providers on a CAHPS measure, increased utilization of hospice in the last 30 days, and decreased hospital, emergency department utilization, and overall health care spending. 42 This approach holds promise, yet communication of prognosis was outside the scope of this intervention. Other participants proposed that SIC should be clinician led because they are best positioned to help patients understand their prognosis and treatment options and can most effectively translate the conversation into care planning.…”
Section: Challenges Recommendations and Future Researchmentioning
confidence: 99%
“…A recent intervention using a lay facilitator demonstrated statistically significant differences in goals of care documentation, overall rating of providers on a CAHPS measure, increased utilization of hospice in the last 30 days, and decreased hospital, emergency department utilization, and overall health care spending. 42 This approach holds promise, yet communication of prognosis was outside the scope of this intervention. Other participants proposed that SIC should be clinician led because they are best positioned to help patients understand their prognosis and treatment options and can most effectively translate the conversation into care planning.…”
Section: Challenges Recommendations and Future Researchmentioning
confidence: 99%
“…It has been successfully utilized in numerous countries to improve access to care. Utilizing task shifting and training multiethnic CHWs to provide aging adult services is an innovative and economical way, to fulfill the large and growing need for complex illness supportive services of community‐dwelling older adults. The World Health Organization defines a community or lay health worker as a member of the community who has received some training to promote health or to carry out some healthcare services but is not a healthcare professional.…”
Section: Strategies To Improve Care Of Diverse Older Adults Within Thmentioning
confidence: 99%
“…An example of a successful training model is the Stanford In‐Reach for Successful Aging and End‐of‐Life (iSAGE) minifellowship, an 80‐hour blended learning program that combines acquisition of knowledge as well as mentored field work to acquire skills. An iSAGE‐trained CHW successfully delivered an intervention to seriously ill cancer patients that resulted in increased goals‐of‐care documentation, improved patient satisfaction, and reduction in healthcare use and costs in later years and at the end of life. A Spanish version of the iSAGE training has been developed and is being used to train “ promotoras” to assist patients in documenting what matters most to them and complete advance care planning.…”
Section: Strategies To Improve Care Of Diverse Older Adults Within Thmentioning
confidence: 99%
“…At six months, the study demonstrated greater goals of care documentation and hospice use, and lower acute care use among patients in the intervention as compared to the control. It was also found that this intervention decreased healthcare expenditure for the VA system, suggesting that this may be a cost-effective model from the perspective of the payor[ 50 ]. Further studies of lay health care worker interventions in low income populations in the United States are ongoing[ 51 , 52 ].…”
Section: Patient Navigation and Community Health Workersmentioning
confidence: 99%